2005
DOI: 10.1002/pon.901
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary melanoma and predictive genetic testing: why not?

Abstract: Rational and emotional motivation for non-participation in the genetic test for hereditary melanoma was found. Emotionally motivated individuals may be reluctant to disseminate genetic risk information. Rationally motivated individuals were better informed than emotionally motivated individuals. It is suggested that a leaflet is added to the invitation letter to enhance informed decision-making about genetic testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 27 publications
3
19
0
Order By: Relevance
“…Test decliners were more worried of the test result, of facing difficult decisions after testing and did not expect the test result would relieve their worries over melanoma. This is in line with our earlier study in which we found older age, parenthood and lower anxiety levels to differentiate counselees from non-visitors [21].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Test decliners were more worried of the test result, of facing difficult decisions after testing and did not expect the test result would relieve their worries over melanoma. This is in line with our earlier study in which we found older age, parenthood and lower anxiety levels to differentiate counselees from non-visitors [21].…”
Section: Discussionsupporting
confidence: 93%
“…The p16-Leiden families reside in a relatively secluded religious area of the Netherlands. Although we did not have information about the motivation of those who did not participate in the psychological part of our study we have previously reported on individuals at risk who did not opt for counseling at all and found that these individuals also had distress levels below population level and did not opt for counseling out of rational and emotional motives [21]. However, the findings may be different for other melanoma families, for which the causative gene and its risk estimates may not be as well established.…”
Section: Discussionmentioning
confidence: 98%
“…We found that respondents experienced annual EUS and MRI investigations as ‘not’ uncomfortable or only ‘slightly’ uncomfortable and dread their next EUS investigations less as surveillance progressed while having decreasing worries about cancer and having normal and stable levels of anxiety and depression. These results are in line with the psychological burden of surveillance for other inherited forms of cancer .…”
Section: Discussionsupporting
confidence: 82%
“…This was assessed using 20 items generated from the published literature, 62 an expert panel, and our previous findings. 35,36 Participants were asked to indicate the extent to which each possible reason for not attending genetic counseling reflected their experience, using a 4-point Likert scale from 0 ("No agreement") to 3 ("Completely agree").…”
Section: Reasons For Not Attending Genetic Counselingmentioning
confidence: 99%